Without Limits Svetlana Zakharova in conversation - Meisner, Nadine (Dance Books Ltd., Alton,Hampshire (UK), 2006)
Bolshoi ballerina Svetlana Zakharova interview in Moscow. PALABRAS CLAVE: Svetlana Zakharova, Bolshoi, biography.